Expression and purification of the recombinant porcine NK-lysin in Pichia pastoris and observation of anticancer activity in vitro. Issue 1 (2nd January 2016) - Fan, Kuohai; Li, Hongquan; Wang, Zhirui; Du, Wenjuan; Yin, Wei; Sun, Yaogui; Jiang, Junbing
ABSTRACT: Natural killer (NK)-lysin, a broad-spectrum antimicrobial peptide, has antitumor and antibactericidal activities against both gram-positive and gram-negative bacteria. In this study the recombinant porcine NK-lysin was expressed and purified in the Pichia pastoris system, and then 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide was used to assess its anticancer activity in vitro . The results showed that the recombinant porcine NK-lysin possesses potent antitumor activity against the human hepatocellular carcinoma cell line SMMC-7721 in a time- and dose-dependent manner, but has negligible hemolysis activity against human erythrocytes. Scanning electronic microscopy was used to directly observe the ultrastructure of SMMC-7721 cells treated with NK-lysin; untreated cells showed lamellipodia and filopodia scattered with the cell surface, with good cell–cell contacts among neighboring cells. In contrast, treated tumor cells exhibited marked alterations in cell morphology, and cell–cell contacts disappeared among neighboring cells. Compared with the untreated tumor cells, the tumor cells treated with NK-lysin for 12 and 24 hr were suppressed for the expression of fascin 1. Thus, the recombinant porcine NK-lysin potentially could be developed as a therapeutic agent for inhibiting tumor growth.